Modelos de ambidestria e desempenho em inovação: um estudo exploratório no grupo Saint-Gobain - Pinto, Rodrigo Amantea de Andrade (2021)
Studies suggest that to survive changes in the business environment, organizations must become ambidextrous. An ambidextrous organization combines exploitation efforts, which concern the refinement of the current businesses and thus involve control, certainty, reduction of variance and increased efficiency, with exploration efforts, which concern new opportunities and, therefore, involve experimentation, search, and discovery. For the balancing of exploration and exploitation, the organization can adopt the contextual, sequential, or structural model, and each of them is accompanied by advantages and limitations. Because it is an emerging field, there are few studies on how organizations seek and develop ambidexterity and what its impacts on innovation outcomes. This paper seeks to fill these gaps, based on a single case study of the Saint-Gobain group, a complex organization with a history of success in adaptation over the years. As a result, it was possible to relate the environmental and organizational antecedents of ambidexterity with the different models for its implementation, addressing in a single study its structural, sequential, and contextual models, differently from previous studies, focused on a specific model of ambidexterity. This study aimed to point out the situations in which each model can be adopted as a response environmental factors that are either clear and expected to happen in the short-term, or those uncertain and without clear expectation to happen, as well as in a context in which organizational factors are favorable or unfavorable, demanding resources and management practices not in force. In addition, it was possible to analyze the impact of the different models of ambidexterity on innovation performance, identifying its impact on innovations in the core, adjacent and transformational innovations. As a contribution to the theory, a conceptual model was proposed in which the environmental and organizational antecedents, including the ambition of innovation, serve as the basis for adopting different models of ambidexterity. The model was presented to the company studied and proved useful to organize innovation, prioritize the flow of innovation, also serving as a basis to improve organizational design.